The North water [videorecording (DVD)] - O'Connell, Jack, 1989-; Farrell, Colin, 1976-; Graham, Stephen, 1973-; Spruell, Sam; Møller, Roland, 1972-; Mullan, Peter; Courtenay, Tom; Lamont, Gary, 1985-; McGuire, Ian (BBC, 2022)
Hoping to escape the horrors of his past, disgraced ex-army surgeon Patrick Sumner signs up as the ship's doctor on an ill-fated Arctic whaling expedition. Soon he's confronted by a new horror, the brutish killer Henry Drax. When Sumner and his crewmates are left stranded on the merciless Arctic wasteland, he discovers just how far he's prepared to go against the savagery of nature and man.